Prevalence of Ureaplasma urealyticum, Chlamydia trachomatis, Neisseria gonorrhoeae and herpes simplex virus in Beijing, China. (3rd December 2018) - Liang, Y. Y.; Zhai, H. Y.; Li, Z. J.; Jin, X.; Chen, Y.; Chen, S. P.
Abstract: The prevalence of sexually transmitted infection (STI) pathogens in Beijing, China, is rarely reported. In this study, 34 911 symptomatic outpatients with suspected genital infections who attended outpatient clinics in a tertiary care hospital were included to investigate the updated prevalence of Ureaplasma urealyticum (UU), Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) and herpes simplex virus (HSV) from 1 January 2013 to 31 December 2016 in Beijing, China. Results indicated that a decrease trend (UU, CT, NG and HSV) in male and an increase trend (UU, CT and NG) in female were observed during the period. Patients aged 20–39 years old were mostly affected by these pathogens, while the prevalence in patients aged 20–29 years old was the highest, The prevalence of UU in male was significantly lower than in female (31.5% vs. 49.3%, P < 0.05), while the prevalence of NG in male was significantly higher than in female (2.5% vs. 0.8%, P < 0.05). In patients with co-infections, 60.6% of male and 71.4% of female were co-infected by UU + CT. In total, 11.9% and 88.1% of patients with HSV infections were confirmed to be infected by HSV-1 and HSV-2. This study could contribute to a better understanding of the current epidemiological features of UU, NG, CT and HSV among symptomatic patients attending an outpatient clinic in Beijing, China, and thus facilitate to develop more effective intervention, prevention and treatment of STI.